Deep cut : science, power, and the unbuilt interoceanic canal - Keiner, Christine, 1971- (Since 1970., 2020)
"The Atlantic-Pacific Central American sea-level canal is generally regarded as a spectacular failure. However, Deep Cut examines the canal in an alternative context, as an anticipated infrastructure project that captured attention from the nineteenth through the late twentieth centuries. Its advocates included naturalist Alexander von Humboldt, physicist Edward Teller, and U.S. presidents John F. Kennedy, Lyndon Johnson, and Jimmy Carter. The waterway did not come to fruition, but as a proposal it served important political and scientific purposes during different eras, especially the years spanning the Cold War and the "environmental decade" of the 1970s."--Publisher web site